2011
DOI: 10.1016/j.ydbio.2010.11.033
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of mouse oocyte microtubule and organelle dynamics by PADI6 and the cytoplasmic lattices

Abstract: Organelle positioning and movement in oocytes is largely mediated by microtubules (MTs) and their associated motor proteins. While yet to be studied in germ cells, cargo trafficking in somatic cells is also facilitated by specific recognition of acetylated MTs by motor proteins. We have previously shown that oocyte-restricted PADI6 is essential for formation of a novel oocyte-restricted fibrous structure, the cytoplasmic lattices (CPLs). Here, we show that α-tubulin appears to be associated with the PADI6/CPL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
66
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(71 citation statements)
references
References 47 publications
3
66
0
2
Order By: Relevance
“…Recently, we found that α-tubulin associates with PAD6 at the lattices, and that PAD6 deletion causes altered microtubule formation and a dramatic suppression of stable microtubules. Further, we found that microtubule mediated organelle repositioning during oocyte maturation was defective in PAD6 null mice, suggesting that PAD6 and the lattices play a critical role regulating microtubule-based activities during oocyte maturation and, potentially, during early development [70]. While other PAD isoforms have not been previously described in normal ovaries, recent studies show PAD4 expression appears to be upregulated in ovarian tumors.…”
Section: Ovarymentioning
confidence: 68%
“…Recently, we found that α-tubulin associates with PAD6 at the lattices, and that PAD6 deletion causes altered microtubule formation and a dramatic suppression of stable microtubules. Further, we found that microtubule mediated organelle repositioning during oocyte maturation was defective in PAD6 null mice, suggesting that PAD6 and the lattices play a critical role regulating microtubule-based activities during oocyte maturation and, potentially, during early development [70]. While other PAD isoforms have not been previously described in normal ovaries, recent studies show PAD4 expression appears to be upregulated in ovarian tumors.…”
Section: Ovarymentioning
confidence: 68%
“…A recent study revealed reduced expression of Mater in NSN oocytes associated with a deficiency of cytoplasmic lattices (CPLs) in their cytoplasm (MONTI et al 2013). Such a defect in the cytoplasmic architecture of NSN oocytes could significantly reduce their development potential since CPLs were identified as the sites of ribosomal storage (YURTTAS et al 2008) and their function in the positioning and movement of organelles in the oocytes and early embryos was also suggested (KAN et al 2011). On the other hand, a study using nuclear transfer between prophase oocytes revealed the importance of both the cytoplasmic and the nuclear components in determining the high developmental potential of SN oocytes (INOUE et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17][18] Regarding the molecular composition of the lattices, older studies suggested that the lattices were largely comprised of intermediate filaments, however more recent studies suggest that the lattices are also associated with microtubules. 19 In addition to their cytoskeletal composition, older and more recent studies have suggested that one function of the lattices is to store a pool of ribosomes that is needed for early cleavage divisions. Perhaps most interestingly, the CPLs undergo extensive spatial reorganization at fertilization, compaction, and blastocyst formation.…”
Section: Introductionmentioning
confidence: 99%